IMPLEMENTASI PEMBELAJARAN DIFERENSIENSI PADA KEGIATAN INTRAKULIKULER, KO-KULIKULER/P5 DAN EKSTRAKULIKULER DENGAN STRATEGI VIANESTIK - Sri Kis Untari (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Differentiated learning is learning that accommodates the needs of students, with the teacher facilitating students according to their needs. As a learning leader at SDN Margorejo I/403 Surabaya, the application of differentiated learning at every level and even every teacher is required to implement it in their respective classes. The application of differentiation learning will have a good impact on schools, classes, and especially on students. In its application, teachers at SDN Margorejo I/403 need to think about reasonable actions that will be taken later, because differentiated learning does not mean learning by providing different actions for each student, as well as learning that differentiates between smart and less intelligent students. SDN Margorejo I/403 Surabaya is one of the objects of research and proving the usefulness of teacher guidance in the implementation of differentiation learning in intracurricular, co-curricular/p5, and extracurricular activities with the Vianestik strategy in educational units to be implemented properly and optimally so as to have a positive impact. significant for schools, classes, and students.